The Liposuction-Induced Effects on Adiponectin and Selected Cytokines Are Not Affected by Exercise Training in Women - Marina Yazigi Solis; Guilherme Giannini Artioli; Eduardo Montag; Vitor de Salles Painelli; Fábio Lopes Saito; Fernanda Rodrigues Lima; Hamilton Roschel; Bruno Gualano; Antonio Herbert Lancha Junior; Fabiana Braga Benatti (International Journal of Endocrinology)
It has been suggested that the abrupt liposuction-induced decrease in adipose tissue could affect adipokine secretion pattern. We hypothesized that exercise training could positively impact adipokine metabolism following liposuction. The aim of this study was to investigate the effects of liposuction on inflammation-related adipokines in women who were either exercise-trained or remained sedentary after surgery. Thirty-six healthy normal-weight women underwent an abdominal liposuction and two months after surgery were randomly allocated into two groups: trained (TR, n=18, four-month exercise program) and nontrained (NT, n=18). Inflammation-related adipokine serum levels (TNF-α, IL-6, IL-10, and adiponectin) and abdominal and thigh subcutaneous adipose tissue (scAT) mRNA levels were assessed before (PRE) and six months after surgery (POST6). TNF-α, IL-6, and IL-10 serum levels were unchanged in both groups. In contrast, TNF-α, IL-6, and IL-10 mRNA levels in scAT were increased, whereas adiponectin scAT mRNA and serum levels were decreased at POST6 (P<0.05, main effect for time). No changes were observed in mRNA levels of MCP-1, CD14, and CD68 in any of the groups. In conclusion, liposuction downregulates adiponectin scAT gene expression and serum levels and upregulates scAT gene expression of inflammation-related genes six months after surgery in normal-weight women, irrespective of exercise training.